Efficacy and safety of platelet-rich plasma injections for the treatment of osteoarthritis: a systematic review and meta-analysis of randomized controlled trials - Xiong, Yongqing; Gong, Cheng; Peng, Xumiao; Liu, Xianlei; Su, Xinda; Tao, Xi; Li, Ying; Wen, Youliang; Li, Wei (Frontiers in Medicine, 2023)
In recent years, platelet-rich plasma (PRP) injections for osteoarthritis (OA) have been widely promoted in clinical practice, but their effectiveness is controversial. Therefore, we conducted a meta-analysis of relevant randomized controlled trials (RCTs) to determine the efficacy and safety of PRP injections for the treatment of OA.We searched databases including Embase, Web of Science, Medline, PubMed, and the Cochrane Library for relevant studies. Two researchers (YQX and CG) performed literature screening, baseline data extraction, literature quality assessment, and heterogeneity analysis of RCTs from the retrieved studies. Based on the magnitude of heterogeneity I 2 , random-effects or fixed-effects models were selected for the meta-analysis.We included 24 RCTs comprising 1344 patients with OA who met the inclusion criteria, with the main types of morbidity being knee osteoarthritis (KOA), hip osteoarthritis (HOA), ankle osteoarthritis (AOA), and temporomandibular joint osteoarthritis (TMJOA). Our results indicate that PRP injections were effective in improving Visual Analogue Scale (VAS) pain scores in patients with KOA, HOA, and AOA compared to controls (AOA, MD=-1.15, CI=95% [-1.74, -0.56], I 2 =40%,